Descartes e a morte de Deus - Bitencourt, Joceval Andrade (2008)
The present work attempts to show the possibilities and limits of the cartesian metaphysics. It has as its main aim, but not the only one, to investigate the possibility of assining to the philosophy of Descartes the posture through which the death of God is inaugurated in western culture. The final result, either in science or in cartesian metaphysics, is the assertion of man as the centre around which all knowledge has to gravitate, knowledge that has in natural reason s authonomy its original cause. The cogito affirming, through the fundaments of the method inspired by mathematical laws, the first truth, subordinates all the other truthes, either about God or about the world, to this first one. Descartes has excluded God from his science. This last one proceeds, notwithstanding any instances external to natural reason s order. If there is a God in cartesian metaohysics, it is not possible to identify him to the Christian God, transcedent 8 mistery, who reveals himself to man, who receives him in faith. The cartesian methaphysics God is only a logical principle, a rational fundament, required by the rules of the method, to which he is subordinated. Thus, the God whom Descartes presents to the world through his metaphysics, is already not the God of religion; he is, according to Pascal s expression, the God of the wise and of the philosophers. The death of God appears, them, as a direct consequence of man s affirmation; legitimating reference of all true konowledge, mainly that which claims to present it self as science. It would be in cartesian metaphysics, in ist own structuration, even if this was not Descartes own explicit intention, that, for the first time, the death of God happened in western philosophical thought